The Effect Of Learning Stress In The Faculty Of Medicine On The Arising Of Acne Vulgaris In Students Of The Faculty Of Medicine YARSI University And Its Review From The Islamic View - Neil Author; Dian Widiyanti; Muhammad Arsyad (Junior Medical Journal, 2023)
Stress is an emotional mental disorder that a person faces because of pressure. Stress is an emotional mental disorder that a person faces because of pressure. Psychosocial stressors can cause physical pain, such as headaches, dizziness, pimples, and so on. The purpose of this research is knowing the effect of stress studying at the Faculty of Medicine with the emergence of acne vulgaris in students of the Faculty of Medicine, YARSI University. The type of research that will be used in this study is the observational analytic method. The population in this study were students of class 2020 and 2021 at the Faculty of Medicine, YARSI University. Determination of the sample to be carried out is by simple random sampling. This study used univariate and bivariate analysis methods. Univariate analysis to describe the characteristics of respondents, the incidence of learning stress and acne vulgaris. The results showed that respondents who experienced academic stress based on the Scale for Assessing Academic Stress questionnaire were 62 students (39.5%). Respondents who suffered from acne vulgaris based on the Global Acne Grading System questionnaire were 133 students in the mild category and 5 students in the moderate category. The results of this study indicate that there is no relationship between stress and the incidence of acne vulgaris in Yasri University Medical Faculty Students Class of 2020-2021. In Islam, everyone will not escape from being given trials by Allah SWT. So in facing trials a Muslim needs to have patience and always think positively.